2005
DOI: 10.1152/ajpendo.00600.2004
|View full text |Cite
|
Sign up to set email alerts
|

A common mitchondrial DNA variant is associated with thinness in mothers and their 20-yr-old offspring

Abstract: Cull, and Jo Poulton. A common mitchondrial DNA variant is associated with thinness in mothers and their 20-yr-old offspring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
11
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 38 publications
1
11
1
Order By: Relevance
“…Despite a sample size substantially larger than that deployed in previous studies of variation in the OriB region, we have been unable to substantiate previous associations with birth weight (16), ponderal index (7,16), placental weight (12), adiposity (12,13), or insulin sensitivity (11,14,15).…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations
“…Despite a sample size substantially larger than that deployed in previous studies of variation in the OriB region, we have been unable to substantiate previous associations with birth weight (16), ponderal index (7,16), placental weight (12), adiposity (12,13), or insulin sensitivity (11,14,15).…”
Section: Discussioncontrasting
confidence: 87%
“…Second, the distribution of positive findings has been patchy, with only limited replication (in the strict sense of same allele, same phenotype). For example, three recent case-control studies (8,16,18) could not replicate previously reported associations between mt16189 and T2D (10,11), and whereas the C-tract has been associated with thinness in early life (12), the association may be reversed in later life (12,13). Third, many studies have used genotyping methods susceptible to error or liable to miss potentially relevant variation elsewhere in the OriB region (e.g.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…The small-size infants, particularly those harbouring the 16189 variant, were subsequently found to have greater early postnatal catch-up growth in comparison with the age-matched infants not harbouring this mtDNA variant. Furthermore, three additional studies from England and Australia found associations between the presence of the 16189 variant and thinness, increased insulin resistance or development of type 2 diabetes in adult life 2 6 19. Recently, increased risk of type 2 diabetes in subjects harbouring the mtDNA 16189 poly-C variant has been observed in many Asian countries 20.…”
Section: Discussionmentioning
confidence: 99%